Kefektifan Sedasi antara Campuran Ketamin Propofol (Ketofol), dan Propofol Fentanil pada Prosedur Endoscopic Retrograde Cholangiopancreatography (ERCP) - Sugiarto, Adhrie; Perdana, Aries; Jefrey Tuhulele, Norman Rabker (Majalah Anestesia dan Critical Care, 2016)
Sedasi adekuat diperlukan untuk menjaga kedalaman sedasi dan analgesia serta mengendalikan pergerakan pasienselama prosedur ERCP. Propofol merupakan sedasi yang tanpa efek analgesia namun memiliki efek depresikardiovaskular dan respirasi yang tergantung dosis. Penambahan ketamin dosis kecil diharapkan menurunkankebutuhan dosis propofol dalam mempertahankan kedalaman sedasi, analgesia, kestabilan hemodinamik danrespirasi. Penelitian ini membandingkan keefektifan sedasi antara campuran ketamin-propofol (ketofol) danpropofol-fentanil pada prosedur ERCP. Penelitian ini adalah uji klinis acak tersamar ganda, 36 pasien dewasayang menjalani prosedur ERCP, dibagi menjadi dua kelompok yaitu kelompok KF (n=18) yang mendapatkanketofol 1:4 dalam semprit 50 mL, serta kelompok PF (n=18) yang mendapatkan fentanil 1 mcg/kgBB dan propofoldalam semprit 50 mL. Kedalaman sedasi diukur dengan Ramsay Sedation Scale. Hasil penelitian didapatkan reratakonsumsi propofol permenit, kelompok ketofol lebih rendah bermakna dibanding dengan kelompok propofolfentanil (p<0.05). Jumlah kebutuhan fentanil pada kelompok ketofol lebih rendah dibanding dengan kelompokpropofol-fentanil (p<0.05). Mula kerja dan waktu pulih pada kelompok propofol-fentanil lebih cepat dibandingdengan kelompok ketofol (p<0.05). Kejadian hipotensi pada kedua kelompok tidak berbeda bermakna (p>0.05).Tidak didapatkan kejadian desaturasi dan mual/muntah pada kedua kelompok. Simpulan adalah ketofol lebihefektif daripada propofol-fentanil untuk kedalaman sedasi dan analgesia serta memiliki efek samping yangminimal. Kata kunci: ERCP, Propofol, ketamin, fentanil, sedasi, analgesia The effectiveness of sedation is the ability of the drugs to maintain sedation depth and analgesia, and to controlpatients movements during ERCP procedure. Propofol is a sedative agent that has no analgesia effect and hasa dose-dependent cardiovascular and respiratory depressant effects. The addition of small dose of ketamin isexpected to reduce the required dose to maintain hemodinamic and respiratory stability. This study comparedthe effectiveness of sedation between 1:4 ketamin propofol mixtures (ketofol) and propofol-fentanyl in ERCPprocedure. This research a double blind randomised clinical trial was done in 36 adult patients who underwentERCP procedure, which were divided into two groups: KF group (n = 18), which were treated with ketofol 1:4in a 50 mL syringe, and PF group (n = 18) which were treated with fentanil 1 mcg/kgBW and propofol in a 50mL syringe. The depth of sedation was measured by Ramsay Sedation Scale (RSS). The average consumption ofpropofol per minute of ketofol group was significantly lower than fentanyl propofol group (p<0.05). The medianfentanyl consumption of ketofol group was significantly lower than fentanyl propofol group (p<0.05). The onsetand the recovery time in fentanyl propofol group were faster than ketofol group (p<0.05). There was no significantdifferent in the incidence of hypotension in both groups (p>0.05). There were no desaturation events or nausea/vomiting in both groups. Conclution ketofol was more effective than fentanyl-propofol mixture in maintaining thedepth of sedation and analgesia and has minimal side effects. Key words: Analgesia,ERCP, fentanyl, ketamine, propofol, sedation Reference Adler DG, Baron TH, Davila RE, Egan J, Hirota WK, Leighton JA, et al. ASGE guideline: the role of ERCP in diseases of the biliary tract and the pancreas. Gastrointest Endosc. 2005;62(1):1–8. Glomsaker TB. Endoscopic Retrograde Cholangiopancreatography (ERCP) in Norway, University of Bergen, 2013. Available at http://www.ivs.no/downloads/ thesis_Glomsaker.pdf, accessed on October 24, 2014 Chainaki IG, Manolarki MM, Paspatis GA. Deep sedation in gastrointestinal endoscopy, World J Gastroentero, 2011, 3 (2): 34–9. Sumaratih L. Perbandingan keluaran antara teknik pemberian propofol bolus berkala dengan Target Controlled Infusion pada pasien endoskopi saluran cerna di RSUPN Cipto Mangunkusumo, Departemen Anestesiologi dan Terapi Intensif Fakultas Kedokteran Universitas Indonesia, Jakarta, 2013. Wang Y, Jiang X, Pan L, Dong S, Feng Y, Prajapati SS, et al. Randomized double-blind controlled study of the efficacy of ketofol with propofolfentanyl and propofol alone in ttermination of pregnancy. Afr. J.Pharm. pharmacol.2012;6(34):2510–14. Coulter FLS, Hannam JA, Anderson BJ. Ketofol dosing simulations for procedural sedation, Pediatr Emerg Care, 2014;30(9): 621–30. Andolfatto G, Willman E. A prospective case series of pediatric procedural sedation and analgesia in the emergency department using single-syringe ketamin propofol (ketofol), Acad Emerg Med, 2010;17:194–201. Hassenein R, El-Sayed W. Ketamin/propofol versus fentanyl/propofol for sedating obese patients undergoing Endoscopic Retrograde Cholangiopancreatography (ERCP), Egypt J Anesth, 2013;29:207–11. Thom G. The evolving role of ketofol and its use as sedation agent in PSA in children: systemic review, 2013. Available at http://sedationspecialists.co.za/wpcontent/uploads/2013/07/Ketofol-in-sedationnew-developments_Dr-George-Thom.pdf, accessed on October 11, 2014.